Heterologous overexpression of the cyanobacterial alcohol dehydrogenase sysr1 confers cold tolerance to the oleaginous alga Nannochloropsis salina - Lim, Jong-Min; Jung, Sokyong; In, Jae-Sun; Park, Youn-Il; Jeong, Won-Joong (Frontiers in Plant Science, 2023)
Temperature is an important regulator of growth in algae and other photosynthetic organisms. Temperatures above or below the optimal growth temperature could cause oxidative stress to algae through accumulation of oxidizing compounds such as reactive oxygen species (ROS). Thus, algal temperature stress tolerance could be attained by enhancing oxidative stress resistance. In plants, alcohol dehydrogenase (ADH) has been implicated in cold stress tolerance, eliciting a signal for the synthesis of antioxidant enzymes that counteract oxidative damage associated with several abiotic stresses. Little is known whether temperature stress could be alleviated by ADH in algae. Here, we generated transgenic lines of the unicellular oleaginous alga Nannochloropsis salina that heterologously expressed sysr1, which encodes ADH in the cyanobacterium Synechocystis sp. PCC 6906. To drive sysr1 expression, the heat shock protein 70 (HSP70) promoter isolated from N. salina was used, as its transcript levels were significantly increased under either cold or heat stress growth conditions. When subjected to cold stress, transgenic N. salina cells were more cold-tolerant than wild-type cells, showing less ROS production but increased activity of antioxidant enzymes such as superoxide dismutase, ascorbate peroxidase, and catalase. Thus, we suggest that reinforcement of alcohol metabolism could be a target for genetic manipulation to endow algae with cold temperature stress tolerance.